Colorimetric chemodosimeter based on diazonium-gold-nanoparticle complexes for sulfite ion detection in solution - Du, Jianjun (2013)
A fast and simple colorimetric detection system for sulfite, based on diazonium–gold-nanoparticle(AuNP) complexation, has high selectivity and sensitivity in aqueous media. The positively charged diazonium has affinity for the AuNP surface due to an electrostatic effect, which prevents AuNPs from aggregating in highly saline solutions. Upon addition of sulfite, the AuNPs are free to aggregate due to the formation of a neutral and insoluble phenylhydrazine derivative.